Risk Factor of Hospital Malnutrition After Pediatric Nutrition Care Management - Miriawati Miriawati; Roedi Irawan; Boerhan Hidayat; Nur Aisiyah Widjaya; Meta Herdiana Hanindita (Health Notions, 2021)
Increased prevalence of Hospital Malnutrition (HM) caused by Pediatric Nutrition Care (PNC) has not been implemented and influenced by several risk factors. The aim was to determine the prevalence and risk factors for gender, age, initial nutritional status, admission diagnosis, and length of stay (LOS) of HM after PNC. A cross sectional study was conducted from May 1, 2017 to May 1, 2018 by reviewing the medical record of children who were treated in the pediatric ward Dr. Soetomo Surabaya. The sampling method is total sampling. Hospital malnutrition was defined as weight loss ≥ 2% for LOS